2011
DOI: 10.1113/expphysiol.2010.055269
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between force and size in human single muscle fibres

Abstract: When the contractile properties of single muscle fibres are studied, force is typically normalized by fibre cross-sectional area and expressed as specific force. We studied a set of 2725 chemically skinned human single muscle fibres from 119 healthy adults to determine whether specific force is the optimal way to express the relationship between single-fibre force and size. A linear mixed effects model was used to estimate the slope and slope variability among individuals of log-log plots of force and diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
(25 reference statements)
1
42
0
Order By: Relevance
“…It is reasonable to presume that the great metabolic capacity for ATP supply of these athletic mammals is driven by a greater capacity to consume ATP as a result of a greater skeletal muscle fibre contractile capacity. The amount of absolute force a fibre can produce is directly proportional to its CSA (Woledge et al, 1985;Bottinelli, 2001;Krivickas et al, 2011). Thus, as the majority of morphological studies on the skeletal muscle of these wild animals have reported significantly smaller CSA of the fibres compared with that of humans, our hypothesis was that their fibres would produce less absolute force, but greater specific force.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…It is reasonable to presume that the great metabolic capacity for ATP supply of these athletic mammals is driven by a greater capacity to consume ATP as a result of a greater skeletal muscle fibre contractile capacity. The amount of absolute force a fibre can produce is directly proportional to its CSA (Woledge et al, 1985;Bottinelli, 2001;Krivickas et al, 2011). Thus, as the majority of morphological studies on the skeletal muscle of these wild animals have reported significantly smaller CSA of the fibres compared with that of humans, our hypothesis was that their fibres would produce less absolute force, but greater specific force.…”
Section: Introductionmentioning
confidence: 83%
“…The latter requires equipment that can additionally calculate the depth of a fibre, or measuring diameters in two planes, resulting in two values for diameter that could yield a more accurate measure of CSA. Recently, Krivickas and colleagues (Krivickas et al, 2011) proposed normalising force to fibre diameter, as a better relationship was found using this parameter compared with CSA, suggesting a new normalisation method that would allow for values obtained from different laboratories to be more easily compared. However, it requires a separate investigation to determine whether this would be true across species.…”
Section: Technicalities: Bath Temperatures Of Experiments and Normalimentioning
confidence: 99%
See 1 more Smart Citation
“…Parenthetically, an additional embryonic isoform of myosin may be expressed in some physiological/pathophysiological conditions (D'Antona et al, 2003, 2006). A simple shift in the type of MHC isoform expressed in the fiber will produce different tissue level velocity and tension (force per CSA) characteristics, as faster contracting MHCs (I < IIA < IIX) produce more tension (D'Antona et al, 2003, 2006; Pansarasa et al, 2009; Krivickas et al, 2011). Thus, this myofilament variation can alter whole muscle performance (Thorstensson et al, 1977; Ryushi and Fukunaga, 1986; Harridge et al, 1996).…”
Section: Myosin-actin Cross-bridge (Xb) Interactionsmentioning
confidence: 99%
“…It is often assumed that muscle mass reflects muscle force generating capacity (Jones, Bishop, Woods, & Green, 2008), but neurological factors may interfere with force production in humans as well (Degens, Erskine, & Morse, 2009). Moreover, specific force or muscle force per physiological cross sectional area (PCSA) tends to be higher in type 2 than type 1 muscle fibres (Bottinelli, Schiaffino, & Reggiani, 1991;Krivickas, Dorer, Ochala, & Frontera, 2011;Stienen, Kiers, Bottinelli, & Reggiani, 1996;Young, 1984). Little effort has been spent in search for other factors modulating specific force.…”
Section: Introductionmentioning
confidence: 99%